2005
DOI: 10.2106/jbjs.c.00974
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Preoperative Radiation for Prophylaxis Against Heterotopic Ossification

Abstract: Preoperative irradiation to prevent heterotopic ossification optimally should be administered twenty-four hours before the operation. This latency period probably allows expression of radiation-induced sublethal mutations in the genetic code of pluripotential stem cells and precludes differentiation to osteoblastic cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…The mRNA and protein levels for a number of molecules were significantly altered within 2 weeks of injury. Myofibroblast numbers, the chance of posttraumatic contractures and to institute nonsteroidal anti-inflammatory therapy or radiation treatment perioperatively, in order to prevent recurrence of heterotopic ossification following surgical releases (Rumi et al 2005, Cohen 2006, Doornberg and Jupiter 2006. These clinical experiences support the early changes in the joint capsule reported in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA and protein levels for a number of molecules were significantly altered within 2 weeks of injury. Myofibroblast numbers, the chance of posttraumatic contractures and to institute nonsteroidal anti-inflammatory therapy or radiation treatment perioperatively, in order to prevent recurrence of heterotopic ossification following surgical releases (Rumi et al 2005, Cohen 2006, Doornberg and Jupiter 2006. These clinical experiences support the early changes in the joint capsule reported in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Early motion after joint injury lessens the severity of contracture and modern internal fixation techniques have advanced this practice in the last century (Doornberg and Jupiter 2006). Methods to prevent heterotopic ossification have to be instituted within a few days of the injury (Rumi et al 2005). We have now investigated early changes in the joint capsule of the animal model of posttraumatic contracture in an attempt to ascertain changes correlated with contracture development.…”
mentioning
confidence: 99%
“…Unfortunately, predicting or preventing the development of HO is very difficult [12][13]. Pharmacological interventions or local radiation therapy have been recommended as prophylaxis for HO, but the result is uncertain and controversial [11,[14][15][16][17][18][19]. We administered oral indomethacin as a routine after each operation because some studies had reported its role in prophylaxis for HO [20][21].…”
Section: Discussionmentioning
confidence: 99%
“…After wound closure, postoperative AP and lateral radiographs of the residual limb were obtained as baseline images. The rats were maintained for 24 weeks, and serial orthogonal radiographs of the residual limb were obtained at 10 days and at 4,8,12,16,20, and 24 weeks. Euthanasia was planned for all animals at 24 weeks.…”
Section: Methodsmentioning
confidence: 99%